Pemberdayaan SDM dalam Peningkatan Kualitas Produksi dan Pemasaran “Kemplang Panggang” Kec. Pemulutan - Pridayani, Annisa (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Human Resource (HR) Empowerment is a key factor in improving the quality of production and marketing of local products. Kemplang Panggang, as one of the leading products in Pemulutan District. Responding to the challenges in improving quality and competitiveness in a wider market. This Community Service Program aims to improve business actors in the aspects of production and marketing through training and mentoring. The methods used include training in hygienic production techniques, improving quality standards, and digital marketing strategies. The results of the activity show an increase in understanding and skills of business actors in implementing good production standards and the use of digital media for marketing. The results of this activity confirm that increasing HR capacity plays an important role in encouraging local business growth and expanding market reach.